Pengendalian Level Air pada Coupled Tank dengan Metode PID Berbasis PLC dan IoT - Fitria Suryatini; Abyanuddin Salam; Selena Natasha (The Indonesian Journal of Computer Science, 2024)
There are many advanced technological discoveries in industry, including the coupled tank. Coupled tanks are several tanks connected to each other. One of the quantities that is often controlled in the industry is the control of water levels. Water level control in a PLC and IoT-based coupled tank system is a medium for controlling and monitoring water levels remotely in real-time. The sensor used is a Differential Pressure Transmitter (DPT) with a pump motor actuator which is connected to an Omron PLC using an inverter. There is a disturbance in the form of setting the control valve opening. The control method used is the PID method with Ziegler-Nichols tuning and trial and error. Both methods analyzed which performance of the system response characteristics was better. It is proven that PID tuning is suitable for water level control of coupled tank systems.